A Systematic Approach to Solving Hatchability and Chick Quality Problems - Gary D. Butcher; Amir H. Nilipour (EDIS, 2003)
A program involving routine analyses of incubating eggs and hatch residue provides a powerful monitoring and diagnostic tool to breeder, broiler, and hatchery managers. This program would allow managers to stay abreast of many problems with breeder performance, egg management, and broiler grow-out. An organized, scheduled program would verify that the processes of egg production and incubation are being done correctly. Data generated by egg breakout analyses provide information of the flock history, details of breeder and hatchery management, and anticipated early broiler performance. This document is VM136, one of a series of the Veterinary Medicine-Large Animal Clinical Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date June 12, 2002.